Flexible Manufacturing with Starch-based Excipient Blends for Early-Stage Drug Product Development - Sandeep Kumar; Barry Friend; Jason Teckoe; Rajan Lad; Simon Lawrence; Sarah Stewart (University of Huddersfield Press, 2023)
Starch-based powder blends are gaining popularity in the pharmaceutical industry due to their inherent process flexibility and compatibility with different manufacturing techniques. In this study, we evaluated the performance of starch-based excipient blends in achieving process flexibility with four commonly used manufacturing techniques, including roller compaction, wet granulation, direct compression, and fluid bed granulation. We also evaluated the compressibility, compactibility, and tabletability of the powders made with these techniques, compressed using a Gamlen™ press. Our results show that the fluid bed process gave the strongest tablet blends, while the roller compaction technique gave the weakest tablet blends. These findings highlight the potential of starch-based excipients in providing flexibility in the manufacturing process for early-stage drug product development.